Gene inactivation in the oral spirochete Treponema denticola: construction of an flgE mutant. - Li, H (1996)
Treponema denticola is implicated in the etiology of periodontal diseases. We now report the construction of a specific flgE mutant of T. denticola ATCC 35405 following electroporation utilizing an erythromycin resistance cassette inserted into an flgE DNA fragment. The resulting mutant displays no visible motility and lacks periplasmic flagella as would be predicted from inactivation of the gene for the flagellar hook protein.